2012
DOI: 10.1534/genetics.111.130286
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Regulation of Glycerolipids in the Yeast Saccharomyces cerevisiae

Abstract: Due to its genetic tractability and increasing wealth of accessible data, the yeast Saccharomyces cerevisiae is a model system of choice for the study of the genetics, biochemistry, and cell biology of eukaryotic lipid metabolism. Glycerolipids (e.g., phospholipids and triacylglycerol) and their precursors are synthesized and metabolized by enzymes associated with the cytosol and membranous organelles, including endoplasmic reticulum, mitochondria, and lipid droplets. Genetic and biochemical analyses have reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
720
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(739 citation statements)
references
References 371 publications
(567 reference statements)
19
720
0
Order By: Relevance
“…Because phospholipid levels are elevated in both tgd1-1 sdp1-4, in which TAG hydrolysis is impaired, and tgd1-1 pxa1-2, in which FA degradation is impaired, it is unlikely that this increase is due to the augmented recycling to TAG into membrane lipids as a result of blocked FA turnover. It is important to note that lipid homeostatic regulation in bacteria (Zhang and Rock, 2008), yeast (Henry et al, 2012), and mammals (Hermansson et al, 2011) is complex and occurs by diverse mechanisms. While we have shown that PDAT1, SDP1 lipase, and lipins are involved in this process in leaves, it is likely that additional components will be uncovered in future research that will lead to a more global understanding of lipid homeostasis in plants.…”
Section: Fa B-oxidation Is Important For Cellular Lipid Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Because phospholipid levels are elevated in both tgd1-1 sdp1-4, in which TAG hydrolysis is impaired, and tgd1-1 pxa1-2, in which FA degradation is impaired, it is unlikely that this increase is due to the augmented recycling to TAG into membrane lipids as a result of blocked FA turnover. It is important to note that lipid homeostatic regulation in bacteria (Zhang and Rock, 2008), yeast (Henry et al, 2012), and mammals (Hermansson et al, 2011) is complex and occurs by diverse mechanisms. While we have shown that PDAT1, SDP1 lipase, and lipins are involved in this process in leaves, it is likely that additional components will be uncovered in future research that will lead to a more global understanding of lipid homeostasis in plants.…”
Section: Fa B-oxidation Is Important For Cellular Lipid Homeostasismentioning
confidence: 99%
“…To date, although most of the enzymatic steps in lipid biosynthesis are defined at the moleculargenetic level in several model organisms (Nohturfft and Zhang, 2009;Chapman and Ohlrogge, 2012;Henry et al, 2012), the signals and mechanisms regulating intracellular lipid homeostasis are less well defined (Nohturfft and Zhang, 2009;Hermansson et al, 2011, Holthuis andMenon, 2014), particularly in plants (Bonaventure et al, 2004;Kunz et al, 2009;Zhang et al, 2009;Fan et al, 2013a;Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation for this is that some of the radiolabel from [ 3 H]serine can be incorporated into PE by mechanisms other than decarboxylation of PS. Serine is used in the biosynthesis of sphingosine and degradation of the sphingosine derivative dihydrosphingosine-1-phosphate by Dpl1p yields ethanolamine phosphate (Henry et al, 2012 (Raychaudhuri and Prinz, 2008). Thus, the percentage of [ 3 H]PS converted to PE in psd1D psd2D cells is the lowest that can be achieved when PS decarboxylation is ablated.…”
Section: Er To Mitochondria Ps Transfer Decreases In Cells Missing Ermentioning
confidence: 99%
“…Thus, the increased amount of PS transfer from ER to mitochondria in cells expressing ChiMERA resulted in an increased steady-state level of PE. Since CDP-diacylglycerol is a precursor for both PI and PS (Henry et al, 2012), it may be that increased PE production from PS in cells expressing ChiMERA depletes the pools of CDP-diacylglycerol available for PI biosynthesis. It was not possible to determine phospholipids levels were altered in the mitochondria from cells expressing ChiMERA since we were unable to isolate purified mitochondria from these cells (not shown), perhaps because they have a substantially increased amount of ER-derived membranes associated with them.…”
Section: An Artificial Er-mitochondria Tether Restores Ps Transfer Inmentioning
confidence: 99%
“…Degradation of TG in yeast is governed by the major lipid droplet (LD)-associated lipases, encoded by TGL3 and TGL4 (4, 12); both enzymes belong to the patatin-domaincontaining family of proteins, members of which play a crucial role in lipid homeostasis also in mammals (13). Multiple additional lipases exist in yeast, but their specific function and contribution to TG homeostasis may be restricted to specific growth conditions (7,14,15).Absence of lipolysis in mutants lacking TGL3 and TGL4 results in up to threefold elevated levels of TG and reduced levels of phosphatidylcholine and sphingolipids (4,12,16,17), indicating that TG breakdown provides precursors for these lipids or generates some regulatory factors required for their synthesis. The rate of phosphatidylinositol (PI) synthesis after readdition of inositol to inositol-starved cells is reduced by 50% in lipase-deficient cells; the boost of PI synthesis under inositol refeeding conditions is completely abolished if de novo FA synthesis is additionally blocked in the lipase mutants by the inhibitor cerulenin (18).…”
mentioning
confidence: 99%